Peran Guru Agama Katolik dalam Membangun Karakter Siswa di SD Negeri Sinar-Suani Kecamatan Idanotae - Sitepanus Zebua; Paulinus Kanisius Ndoa; Yantos Bawamenewi (Journal New Light, 2025)
The theme of this thesis was raised by the researcher because it was motivated by the role of Catholic religious teachers in building student character in schools, the Church and society who often make mistakes in providing an understanding of student character development in school. This happens because it is caused by the views of society and the environment around it. In society, it prioritizes the character of students who are already in school and prioritizes women and even treats women unfairly, resulting in gender injustice. The aim of this research is to determine the characteristics of religious teachers who excel in developing character. Meanwhile, the method used in this thesis is literature review, namely studying the theme of this thesis by utilizing ideas and discussions from books, journals, encyclopedias, Church documents, the internet and other literature. The results of the discussion obtained were that the Church does not agree that there are differences in degrees between men and women. The Church firmly conveys that men and women have equal equality both within the family, the Church and in society. This attitude of the Church comes from God Himself as the Creator of heaven and earth which can be seen in the story of events which illustrates that God created humans as equal, both men and women, even though they are physically different, but men and women were created by God with the same dignity as images of God.